2018
DOI: 10.1002/jgh3.12081
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin D deficiency on eradication rates of Helicobacter pylori infection

Abstract: Background/Aim: Many studies have investigated risk factors other than antibiotic resistance linked to Helicobacter pylori (H. pylori) eradication failure. The aim of this study was to study the effect of serum levels of D) on eradication rates of H. pylori infection. Methods: This study included 150 patients diagnosed with H. pylori gastritis using magnifying narrow-band imaging endoscopy supported by stool antigen test. Serum 25-OH vitamin D levels were measured via the Enzyme-Linked Immune Sorbent assay (EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…Several clinical studies have illustrated that vitamin D analogs may have anti‐ H. pylori antimicrobial effects . Some studies have also found that serum vitamin D levels may have an impact on H. pylori eradication …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several clinical studies have illustrated that vitamin D analogs may have anti‐ H. pylori antimicrobial effects . Some studies have also found that serum vitamin D levels may have an impact on H. pylori eradication …”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D regulates the calcium and phosphorus metabolism needed for bone formation, and the influence of vitamin D on H. pylori infection and eradication rates has recently been widely investigated. Several clinical studies have illustrated that vitamin D analogs may have anti‐ H. pylori antimicrobial effects . Cytological research has also found that vitamin D 3 decomposition product 1 (VDP1) can lyse H. pylori bacterial cells by inducing the collapse of the cell membrane …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our search identified 182 related references, of which 10 papers met our inclusion criteria . The flowchart describing the process of study selection is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%